HUBUNGAN KARAKTERISTIK KELUARGA DENGAN KEJADIAN STUNTING PADA REMAJA DI SMAN 1 SUMATERA BARAT - Engla Pasalina; Hendri Devita; Nirmala Sari; Vitri Yuli Afni Amran; Ira Suryanis; Novi Maya Sari (Poltekkes Kemenkes Medan, 2022)
Stunting prevalence (aged 16-18 years) in Indonesia based on Riskesdas data in 2010, 2013 and 2018 was 31.2%, 31.4% and 26.9%, respectively. West Sumatra is one of the provinces in Indonesia with a fairly high prevalence of stunting in adolescents, namely 18.4% short adolescents and 7.2% very short adolescents. The high prevalence of stunting in West Sumatra is still a big question mark because West Sumatra is rich in plant and animal food sources. One of the cities in West Sumatra as the largest producer of plant and animal food is Padang Panjang City. Stunting is one of the predictors of poor quality of Human Resources. The purpose of this study was to analyze the relationship between family characteristics and the incidence of stunting in adolescents at SMAN West Sumatra Padang Panjang. This research is an analytical survey research with a cross-sectional design. The research population was all students of SMAN 1 West Sumatra Padang Panjang. The sample amounted to 70 people who were taken by accidental sampling technique. Data were analyzed by univariate and bivariate. The results showed that there was no relationship between family characteristics (educational level of father and mother, occupation of father and mother, and number of family members) with the incidence of stunting in adolescents.